Study on Control Optimization for Heavy Haul Train Based on Fuzzy Adaptive PID Control - ZHAO Qiaoni (机车电传动)
Dynamic model was built with 2 HXD1+100 C80 vehicles for the marshaling mode. The table mode of coupler force was established with the in-continuity of smooth unloading over the excessive pattern, and the fuzzy adaptive PID controller was used to control the force deviation and the change rate of the coupler force deviation. The simulation results showed that the actual value of controlled object was consistent with target value. The controller can effectively control the discontinuity of the coupler force loading and unloading process and ensure the safety of train operation based on the accurate dynamic model.